First records of the mealybug Rastrococcus invadens Williams (Hemiptera: Pseudococcidae) in French Guiana and the Americas - Germain, Jean-François; Laplace, Damien; Devarieux, Antonin; Boavida, Conceição (Zootaxa, 2015)
At the end of August 2014, a visitor to the French National Plant Protection service (NPPO) in Cayenne (French Guiana) brought in mango twigs covered with a significant amount of sooty mould. From these branches, the NPPO officers took large numbers of mealybugs from the underside of the leaves (Fig. 1). The sample was sent to the Plant Health Laboratory (LSV) in Montpellier where it was identified as Rastrococcus invadens Williams. This is the first record of this species in French Guiana and in the Americas.